O uso da homeopatia em pacientes com depressão - (:unkn) unknown (Universidade Brasil, 2021)
Created over 200 years ago, homeopathy was developed by Samuel Hahneman from the principle of similarity, which is based on healing by similarity, that is, the healthy individual is exposed to a substance, whether plant, animal or even mineral, the effects shown are reference to using the same diluted or dynamized substance totreat the patient who manifests the same symptoms. Although it has existed for someyears, and is recognized in Brazil as a medicinal therapy, homeopathy still finds a lot of resistance and disbelief, especially due to its lack of knowledge about its action in the body. Depression is a disease that affects millions of people around the world and in Brazil the numbers are growing. The treatment of this disease is carried out through the use of antidepressants and psychotherapy, however, they have many reports of important adverse effects. The present work is a narrative literature review that sought to inform what the specialized health literature says about the use of homeopathy in the treatment of depression. Homeopathic treatment benefits the useras it does not have adverse effects, it is easily accessible and is present in the SUS (Unified HealthSystem).
Keywords: Depressão; Farmacoterapia; Homeopatia; Homeopatia - Farmácia; Farmácia; CS